2022
DOI: 10.1186/s12964-022-00821-7
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically disordered proteins play diverse roles in cell signaling

Abstract: Signaling pathways allow cells to detect and respond to a wide variety of chemical (e.g. Ca2+ or chemokine proteins) and physical stimuli (e.g., sheer stress, light). Together, these pathways form an extensive communication network that regulates basic cell activities and coordinates the function of multiple cells or tissues. The process of cell signaling imposes many demands on the proteins that comprise these pathways, including the abilities to form active and inactive states, and to engage in multiple prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(81 citation statements)
references
References 327 publications
2
79
0
Order By: Relevance
“…Finally, not surprisingly, prediction of the structures of intrinsically disordered proteins (IDPs) and regions (IDRs) is another problem where AlphFold falls short. Disordered proteins (regions) are characterized by broad and heterogeneous ensembles where the differences in the relative conformational stabilities are small, or even minor and the barriers are low. The conformations interconvert, leading to low probabilities of AlphaFold’s reliably capturing those most favored, or the conformational distribution. Nevertheless, leveraging, learning, and mining of the conformations can exploit AI. …”
Section: Introductionmentioning
confidence: 99%
“…Finally, not surprisingly, prediction of the structures of intrinsically disordered proteins (IDPs) and regions (IDRs) is another problem where AlphFold falls short. Disordered proteins (regions) are characterized by broad and heterogeneous ensembles where the differences in the relative conformational stabilities are small, or even minor and the barriers are low. The conformations interconvert, leading to low probabilities of AlphaFold’s reliably capturing those most favored, or the conformational distribution. Nevertheless, leveraging, learning, and mining of the conformations can exploit AI. …”
Section: Introductionmentioning
confidence: 99%
“…SDMs are based on the concept of protein intrinsic disorder, which is defined as a lack of unique structure in part of the whole functional protein [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Multiple computational tools have been developed to predict disorder.…”
Section: Methodsmentioning
confidence: 99%
“…A common trait of ID proteins (IDPs) is the lack of stable, well-defined 3D structure in the absence of a partner or a ligand under physiological pH and ionic strength [ 66 , 67 ]. Related to that, it is not surprising that α-Syn adopts a monomeric, random coil conformation in an aqueous medium, while its interaction with lipid membranes drives the transition of the protein part (N-terminus and NAC region) into defined α-helical structures ( Figure 1 ) [ 60 , 62 ].…”
Section: Alpha-synucleinmentioning
confidence: 99%
“…For inhibition-based studies, high-throughput screening has identified several promising α-Syn aggregation inhibitors [ 211 , 217 ]. Being a dynamic target, disordered α-Syn impedes structure-based drug design [ 67 , 218 ]. Therefore, multiple contact points organised over a large surface area are required for the specific binding of other molecules to α-Syn [ 126 ].…”
Section: Therapies and Strategies Against Pd Related To α-Synmentioning
confidence: 99%